The 'Most Distinguished Envoy of Peace': Averell Harriman and the Vietnam War in the Johnson Years. Issue 1 (1st January 2016) - Colman, Jonathan
Abstract : From 1965 to 1969 the eminent diplomat Averell Harriman was at the forefront of US efforts to achieve a negotiated peace in Vietnam, pursuing numerous initiatives with vigour. He grew frustrated and embittered at how, in his view, President Johnson and his advisers were responsible for missing a number of opportunities for peace. However, recent research indicates that Communist attitudes were at least as much a sticking point. Harriman was also keen to enlist Soviet assistance, but it has become clear that Moscow was ambivalent towards engaging wholeheartedly with the peace effort. The article provides a fresh perspective on Harriman's attempts to bring peace in Vietnam, not least through the use of recent research in Communist archives.